2018
DOI: 10.3791/58187
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Neural Activity and Connectivity Using Intracranial EEG Data with SPM Software

Abstract: Measuring neural activity and connectivity associated with cognitive functions at high spatial and temporal resolutions is an important goal in cognitive neuroscience. Intracranial electroencephalography (EEG) can directly record electrical neural activity and has the unique potential to accomplish this goal. Traditionally, averaging analysis has been applied to analyze intracranial EEG data; however, several new techniques are available for depicting neural activity and intra-and interregional connectivity. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recently, an advanced EEG analysis, utilizing artificial intelligence and/or machine learning techniques, reported an up to 74% true-positive rate for detecting seizure waveforms ( Emami et al., 2019 ) or up to 88% correct prediction of antidepressant effects in patients with major depression ( Jaworska et al., 2019 ). Connectivity analysis with a high temporal resolution (milliseconds), utilized with intracranial recording, demonstrated that inter-regional connectivity between the inferior occipital gyrus and the amygdala could be observed during face recognition ( Sato et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an advanced EEG analysis, utilizing artificial intelligence and/or machine learning techniques, reported an up to 74% true-positive rate for detecting seizure waveforms ( Emami et al., 2019 ) or up to 88% correct prediction of antidepressant effects in patients with major depression ( Jaworska et al., 2019 ). Connectivity analysis with a high temporal resolution (milliseconds), utilized with intracranial recording, demonstrated that inter-regional connectivity between the inferior occipital gyrus and the amygdala could be observed during face recognition ( Sato et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%